2012
DOI: 10.1042/bsr20120042
|View full text |Cite
|
Sign up to set email alerts
|

The endocrine disruptor mono-(2-ethylhexyl)phthalate promotes adipocyte differentiation and induces obesity in mice

Abstract: The environmental obesogen hypothesis proposes that exposure to endocrine disruptors during developmental ‘window’ contributes to adipogenesis and the development of obesity. MEHP [mono-(2-ethylhexyl) phthalate], a metabolite of the widespread plasticizer DEHP [di-(2-ethylhexyl) phthalate], has been found in exposed organisms and identified as a selective PPARγ (peroxisome-proliferator-activated receptor γ) modulator. However, implication of MEHP on adipose tissue development has been poorly investigated. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(106 citation statements)
references
References 53 publications
5
101
0
Order By: Relevance
“…Moreover, di(2-ethylhexyl) phthalate (DEHP) or its metabolite mono-(2-ethylhexyl) phthalate (MEHP) increased adipocyte differentiation in 3T3-L1 cells, (142) (115), murine mesenchymal stem cells (44), and in vivo (142) (62). Few human studies have addressed effects of BFRs on obesity and metabolic syndrome; however, adipocyte differentiation was increased by the BFRs PDBE (397) and BDE-47 (185).…”
Section: Effects Of Pops On At Functionmentioning
confidence: 99%
“…Moreover, di(2-ethylhexyl) phthalate (DEHP) or its metabolite mono-(2-ethylhexyl) phthalate (MEHP) increased adipocyte differentiation in 3T3-L1 cells, (142) (115), murine mesenchymal stem cells (44), and in vivo (142) (62). Few human studies have addressed effects of BFRs on obesity and metabolic syndrome; however, adipocyte differentiation was increased by the BFRs PDBE (397) and BDE-47 (185).…”
Section: Effects Of Pops On At Functionmentioning
confidence: 99%
“…DEHP was recently reported to be a ligand for activation of PPARs and thus might be implicated in adiposity induced by DEHP (Latini et al 2006;Viana Abranches et al 2011). DEHP disrupts the metabolism of fatty acids in adipocytes and thereby promotes their differentiation, ultimately leading to obesity (Desvergne et al 2009;Hao et al 2012;Chiang et al 2015). However, how maternal DEHP exposure induces adiposity in offspring and whether a PPAR-dependent mechanism is involved in this process in our in vivo system remain for further investigation.…”
Section: Discussionmentioning
confidence: 94%
“…mesenchymal stem cells C3H/10T1/2. Mono-(2-ethylhexyl), a metabolite of DEHP, also increased LPL expression in mice adipose tissue (Hao et al, 2012b). However, DEHP caused a significant increase of TAGs (24 h) and PCs (48 and 72 h exposure), particularly of highly unsaturated PCs (>5) of 38 and 40 C atoms, which is in agreement with other studies that reported DEHP (50 M) to enhance the accumulation of PCs in HRP-1 trophoblastic cells after 24 h exposure (Xu et al, 2006).…”
Section: Discussionmentioning
confidence: 95%